Increasing Diversity in Developmental Biology - Unguez, Graciela A.; Bennett, Karen L.; Domingo, Carmen; Chow, Ida (Frontiers in Sociology, 2022)
The demographic profile of the scientific and biomedical workforce in the U.S. does not reflect the population at large (https://ncses.nsf.gov/pubs/nsf21321/data-tables; www.census.gov), raising concerns that there will be too few trained researchers in the future, the scope of research interests will not be broad enough, gaps in equity and social justice will continue to increase, and the safeguards to the integrity of the scientific enterprise could be jeopardized. To diversify the pool of scientists, the Society for Developmental Biology (SDB) developed the Choose Development! Program – a two-summer immersion for undergraduate students belonging to underrepresented (UR) populations in STEM to join the research laboratory of an established SDB member. This research-intensive experience was augmented by a multi-tier mentoring plan for each student, society-wide recognition, professional development activities and networking at national meetings. The strengths of the Choose Development! Program were leveraged to expand inclusion and outreach at the Society's leadership level, the Board of Directors (BOD), which then led to significant changes that impacted the SDB community. The cumulative outcomes of the Choose Development! Program provides evidence that community-based, long-term advocacy, and mentoring of young UR scientists is successful in retaining UR students in scientific career paths and making a scientific society more inclusive.